2009
DOI: 10.1021/ja9044482
|View full text |Cite
|
Sign up to set email alerts
|

Direct versus Hydrogen-Assisted CO Dissociation

Abstract: The mechanism of CO dissociation is a fundamental issue in the technologically important Fischer-Tropsch (F-T) process that converts synthesis gas into liquid hydrocarbons. In the present study, we propose that on a corrugated Ru surface consisting of active sixfold (i.e., fourfold + twofold) sites, direct CO dissociation has a substantially lower barrier than the hydrogen-assisted paths (i.e., via HCO or COH intermediates). This proves that the F-T process on corrugated Ru surfaces and nanoparticles with acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
216
5
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(240 citation statements)
references
References 19 publications
18
216
5
1
Order By: Relevance
“…As it happens for Co and Fe, barriers on Ru catalysts for the unassisted reaction are much higher than those calculated after hydrogenation; this is the case of CO dissociation on the planar (111) terraces and also on low-coordination atoms at step-edge sites. The latter conclusions contrast with results arising from DFT/PW91 studies by van Santen and co-workers, concerning the CO dissociation on stepped Ru(101 � 5) [52], and on open Ru(112 � 1) [53] or Ru(101 � 0)B [54] surfaces, where calculated barriers for CO direct dissociation on low-coordinated sites are only 0.92 eV, 0.67 eV and 0.49 eV, respectively. The barriers on these three Ru surfaces are significantly smaller than that calculated for the reaction on the planar Ru(0001) surface, i.e., 2.35 eV [52]; such barriers are also smaller than those required to cleave the C-O bond via the hydroxymethylidyne or the formyl routes.…”
Section: Co* + H* → Coh* + * (3a)contrasting
confidence: 87%
“…As it happens for Co and Fe, barriers on Ru catalysts for the unassisted reaction are much higher than those calculated after hydrogenation; this is the case of CO dissociation on the planar (111) terraces and also on low-coordination atoms at step-edge sites. The latter conclusions contrast with results arising from DFT/PW91 studies by van Santen and co-workers, concerning the CO dissociation on stepped Ru(101 � 5) [52], and on open Ru(112 � 1) [53] or Ru(101 � 0)B [54] surfaces, where calculated barriers for CO direct dissociation on low-coordinated sites are only 0.92 eV, 0.67 eV and 0.49 eV, respectively. The barriers on these three Ru surfaces are significantly smaller than that calculated for the reaction on the planar Ru(0001) surface, i.e., 2.35 eV [52]; such barriers are also smaller than those required to cleave the C-O bond via the hydroxymethylidyne or the formyl routes.…”
Section: Co* + H* → Coh* + * (3a)contrasting
confidence: 87%
“…In addition, to CO direct dissociation, H atom was found to assist CO dissociation through the formation of intermediate formyl (CHO) on several metals. In the same way, Shetty and coworkers [22] have reported that for compact faces, CHO route is favorable, whereas for corrugated facets, CO direct dissociation might predominate. In the present work we have carried out comprehensive calculations within spin-polarized density functional theory (DFT), to study the dissociative adsorption of H 2 and the effect of the preadsorbed hydrogen in the CO adsorption on Fe(100) under (0, 1/3, 2/3) ML of hydrogen coverages.…”
Section: Introductionmentioning
confidence: 74%
“…3 Theoretical and experimental works to date suggest that a hydrogen-assisted pathway should be more favorable on close-packed surfaces, whereas the carbide mechanism is preferred on stepped and corrugated surfaces. 1,[4][5][6][7][8] Theoretical studies have provided support for dissociation via H x CO intermediates on Ru(0001) (Ref. 5) and Co(0001).…”
Section: Introductionmentioning
confidence: 99%